The Impact of Ownership Structure on Vietnamese Commercial Banks' Profitability - Nguyen, Van-Thep; Liu, Day-Yang (International Journal of Economics and Financial Issues, 2020)
This study aims to check whether ownership structure affects Vietnamese commercial banks' profitability or not and identify factors influencing Vietnamese commercial banks' profitability as well. Utilizing the Bayesian Model Averaging (BMA) model applying for 21 commercial banks in the period 2010-2017, the authors found that bank ownership is statistically significant and the sign of the correlation coefficient is negative, indicating that state-owned commercial banks are less efficient than other commercial banks. Also, the empirical findings show that there are some factors affecting the profitability of commercial banks in Vietnam such as credit risk, capital adequacy ratio, cost-income ratio, staff expenses, and asset growth rate, where credit risk and cost-income ratio have a negative relation to banks' profitability. Keywords: Bank profitability, Bayesian Model Averaging (BMA), Commercial, Ownership structure, Vietnam JEL Classifications: G15, G21, G28 DOI: https://doi.org/10.32479/ijefi.9760